2016
DOI: 10.1007/s00330-016-4674-y
|View full text |Cite
|
Sign up to set email alerts
|

Gd-EOB-DTPA-enhanced MRI for monitoring future liver remnant function after portal vein embolization and extended hemihepatectomy: A prospective trial

Abstract: • The most significant FLR volume increase happens within the first 14 days. • No MRI parameter was able to predict the success of FLR growth. • Our data suggest an early resection about 14 days after PVE. • Routine Gd-EOB-DTPA-enhanced MRI might be suitable to replace ICG-test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…Fourth, there were a large number of patients excluded for having prior history of portal vein embolization. Previous studies showed a significant decrease of signal intensity of the liver lobe after portal vein embolization [ 26 ]. Therefore, in the present study, we decided to investigate the entire liver function, instead of regional liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, there were a large number of patients excluded for having prior history of portal vein embolization. Previous studies showed a significant decrease of signal intensity of the liver lobe after portal vein embolization [ 26 ]. Therefore, in the present study, we decided to investigate the entire liver function, instead of regional liver function.…”
Section: Discussionmentioning
confidence: 99%
“…This could, in combination with liver volume, become a novel tool to assess liver function. [61][62][63][64][65] Very recently, liver surface nodularity, quantitatively assessed on CT using dedicated software, was found to be an independent predictor of post-hepatectomy liver failure after LR for HCC. 66 This promising method needs to be validated in further studies.…”
Section: Improvements In Patient Selection Evaluation Of Liver Functionmentioning
confidence: 99%
“…This could, in combination with liver volume, become a novel tool to assess liver function. [61] , [62] , [63] , [64] , [65] …”
Section: Improvements In Patient Selectionmentioning
confidence: 99%
“…Level of total bilirubin in the bile of the future remnant liver of patients with obstructive jaundice undergoing hepatectomy predicts postoperative liver failure patients undergoing hepatectomy. FRL function is evaluable by volumetry and liver function testing (e.g., indocyanine green [ICG] clearance or technetium-99m-diethylenetriaminepenta-acetic acid-galactosyl human serum albumin single-photon emission computed tomography [99mTc-GSA SPECT)/CT] fusion imaging) [8][9][10][11][12][13] . However, it is sometimes difficult to measure the FRL function in patients undergoing major hepatectomy with bile duct resection because functional parameters are influenced by several other factors, including obstructive jaundice, which is often observed in such patients 14 .…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%